A novel low‐temperature NO removal approach with OH from catalytic decomposition of H2O2 over La1‐xCaxFeO3 oxides. Issue 1 (6th June 2017) - Wu, Bo; Xiong, Yuanquan
Abstract: BACKGROUND: In industrial boilers, the flue gas temperature was below 200°C. The activated temperatures of conventional NO removal approach such as SCR was over 300°C, limiting its application in industrial boilers. In this study, a novel low‐temperature NO removal approach with hydroxyl radicals (OH) from catalytic decomposition of H2 O2 over La1‐ x Cax FeO3 oxides (x = 0, 0.1, 0.3 and 0.5) was proposed. With respect to four as‐prepared catalysts, the catalytic performance was presented and the mechanism was proposed. RESULTS: The catalytic activities of LaFeO3 was higher than the other three catalysts, achieving 89.9% of NO removal efficiency under the optimal operating condition. With the Ca stoichiometry increased, the surface hydroxyl group density and the oxygen vacancy concentration increased while the changes of specific surface area was not monotonic. With respect to the as‐prepared catalysts, the oxygen vacancy played a main and negative role in OH generation and NO removal. The oxygen vacancy accelerated the catalytic decomposition of H2 O2 but not generated OH. The main N‐containing products after oxidation were NO2 and HNO3 . CONCLUSION: This study demonstrated the high activity of LaFeO3 oxides in NO removal and elucidated the correlation between surface property and catalytic performance. © 2017 Society of Chemical Industry